Effect of Rooting Hormone on Stem-Cutting Propagation of Economically Important Garcinia afzelii Tree Species - Anthony Antwi-Wiredu; John Kobina Mensah; Ebenezer Ofori; Padmore Boateng-Ansah; Naomi Adoma Fosu; Joseph Mireku Asomaning (Sustainability Science and Resources, 2025)
Garcinia afzelii, a valuable non-timber forest product (NTFP), is utilised for its edible seeds, chewing sticks, and medicinal properties. However, its survival is threatened by overharvesting, slow growth, and limited natural regeneration, warranting its classification as vulnerable. To mitigate these risks, conservation efforts, including propagation, are essential. This study aimed to develop a vegetative propagation protocol for G. afzelii using stem cuttings treated with varying concentrations of Indole-3-Butyric Acid (IBA), hypothesising that IBA would improve rooting success. Seedlings were cultivated for 12 months in a nursery, after which semi-hardwood stem cuttings were treated with IBA concentrations of 0.0% (control), 0.1%, 0.3%, and 0.8%. These cuttings were propagated in non-mist propagators using river sand as the growth medium, arranged in a Completely Randomised Design (CRD) with five replications per treatment (10 cuttings each). Results indicated that IBA significantly (P ≤ 0.05) enhanced root development, with the 0.8% IBA treatment yielding the longest roots (9.19 cm vs. 6.00 cm in control) and the highest number of lateral roots (59.31 cm vs. 39.46 cm in control). Although the untreated cuttings produced a higher number of roots, they accounted for only 27.90% of root formation, while the three IBA-treated cuttings contributed 72.10%. Conversely, the control cuttings recorded a higher survival rate (80.00%) than the IBA (70.00%). IBA-treated G. afzelii stem cuttings achieved a 62.10% shoot development rate, compared to 37.90% in the untreated cuttings. These findings suggest that IBA promotes shoot and root formation, making it an effective protocol for mass propagation. Thus, IBA application in stem-cutting propagation could optimise root establishment and resource mobilisation, supporting the conservation and cultivation of G. afzelii.